First records of Lithodes longispina Sakai, 1971 (Crustacea: Decapoda: Anomura: Lithodidae) from southwestern Taiwan, including a site in the vicinity of a cold seep - Wang, Teng-Wei; Ahyong, Shane T.; Chan, Tin-Yam (Zootaxa, 2016)
Lithodid crabs (Lithodidae Samouelle, 1819), commonly known as king crabs, are frequent targets of commercial fishing worldwide with most of them living in deep water (Sakai 1971; Ahyong et al. 2010). Lithodes Latreille, 1806, is the second largest genus of lithodid crabs, currently including 29 species worldwide (Ahyong 2010). In Taiwanese waters, however, only two species, L. turritus Ortmann, 1892, and L. formosae Ahyong & Chan, 2010, have been reported (Wu et al. 1998; Ahyong & Chan 2010; Ahyong et al. 2010). We report herein the discovery of L. longispina Sakai, 1971, previously known reliably only from Japan (Sakai 1971; Ikeda 1998; Ahyong 2010), from off southwestern Taiwan, including a specimen collected in the vicinity of a cold seep.